Problems and Solutions of Islamic Da‘wah in Bangladesh - Muhammad, Muhiuddin Khandokar Arif; Hossain, Md Sohrab (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
The research intends to investigate the problems in Islamic Da‘wah in Bangladesh and propose solutions as well as ways to treat and combat them in accordance with the Quranic and Prophetic approaches. These phenomena, which affect the individual, family, and society levels negatively and dangerously, form part of the main issues in Da‘wah that the Bangladeshi people face. The paper attempt to explain this important area, equally, The Prophet’s Sunnah and the Noble Quran provide the most effective guidance for overcoming Da‘wah challenges. The research used an inductive approach to collect legal passages from the Quran and Sunnah, as well as from pertinent sources and references. To reach the study’s objectives, the researcher relied on everything connected to the subject of the study, which deals with the most significant issues confronting Islamic Da‘wah. Additionally, several approaches to overcoming this difficulty are described. The study suggested inviting training facilities as well in order to identify beneficial programs and outstanding credentials that meet peoples’ demands.